A potential role for a novel ZC3H5 complex in regulating mRNA translation in Trypanosoma brucei - Bajak, Kathrin; Leiss, Kevin; Clayton, Christine; Erben, Esteban D. (The journal of biological chemistry, 2020)
In Trypanosoma brucei and related kinetoplastids, gene expression regulation occurs mostly posttranscriptionally. Consequently, RNA-binding proteins play a critical role in the regulation of mRNA and protein abundance. Yet, the roles of many RNA-binding proteins are not understood. Our previous research identified the RNA-binding protein ZC3H5 as possibly involved in gene repression, but its role in controlling gene expression was unknown. We here show that ZC3H5 is an essential cytoplasmic RNA-binding protein. RNAi targeting ZC3H5 causes accumulation of precytokinetic cells followed by rapid cell death. Affinity purification and pairwise yeast two-hybrid analysis suggest that ZC3H5 forms a complex with three other proteins, encoded by genes Tb927.11.4900, Tb927.8.1500, and Tb927.7.3040. RNA immunoprecipitation revealed that ZC3H5 is preferentially associated with poorly translated, low-stability mRNAs, the 5′-untranslated regions and coding regions of which are enriched in the motif (U/A)UAG(U/A). As previously found in high-throughput analyses, artificial tethering of ZC3H5 to a reporter mRNA or other complex components repressed reporter expression. However, depletion of ZC3H5 in vivo caused only very minor decreases in a few targets, marked increases in the abundances of very stable mRNAs, an increase in monosomes at the expense of large polysomes, and appearance of “halfmer” disomes containing two 80S subunits and one 40S subunit. We speculate that the ZC3H5 complex might be implicated in quality control during the translation of suboptimal open reading frames.
Available online 4 January 2021
Gesehen am 10.06.2021